Dampak Pemasaran Di Masa Pandemi Covid-19 Terhadap Kinerja Usaha Mikro Kecil Dan Menengah (Umkm) Di Kota Banjarbaru - sari hepy maharani; Agus Pebrianto; Rohayati (P3M Politeknik Negeri Banjarmasin, 2021)
This study aims to determine the impact of the Covid-19 pandemic on UMKM in the City of Banjarbaru. The dependent variable in this study is the performance of MSMEs while the independent variables include financial aspects, technical & production aspects, marketing aspects, human resources aspects, and technological competency aspects. The survey research was conducted on 106 UMKM which are under the guidance of the Dinas Koperasi, UMKM dan Tenaga Kerja Kota Banjarbaru. The data obtained were then analyzed using multiple linear regression analysis. The results of this study indicate that the cause of the decline in UMKM performance that occurred in almost all UMKM in Banjarbaru was a decrease in the marketing aspect, in this case, a decrease in people's purchasing power caused by the Pandemic.